2015
DOI: 10.1155/2016/8257238
|View full text |Cite
|
Sign up to set email alerts
|

Hericium erinaceus Inhibits TNF‐α‐Induced Angiogenesis and ROS Generation through Suppression of MMP‐9/NF‐κB Signaling and Activation of Nrf2‐Mediated Antioxidant Genes in Human EA.hy926 Endothelial Cells

Abstract: Hericium erinaceus (HE) is an edible mushroom that has been shown to exhibit anticancer and anti-inflammatory activities. We investigated the antiangiogenic and antioxidant potentials of ethanol extracts of HE in human endothelial (EA.hy926) cells upon tumor necrosis factor-α- (TNF-α-) stimulation (10 ng/mL). The underlying molecular mechanisms behind the pharmacological efficacies were elucidated. We found that noncytotoxic concentrations of HE (50–200 μg/mL) significantly inhibited TNF-α-induced migration/in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…However, surprisingly, we suggested in the current study that TAS administration for 2 h prior to TNF-α incubation dramatically prevented the HUVECs from TNF-α-triggered apoptosis by suppressing the overexpression of inflammatory factors, decreasing the viable apoptotic cell ratio, suppressing DNA fragmentation, and reducing caspase-3 activation. In addition, inflammatory cytokine-induced injury is a critical aetiology of TNF-α-induced endothelial damage [33]. Our results verified that TNF-α administration substantially increased the levels of inflammatory cytokines, such as interleukins, MCP-1, MMP-2, and MMP-9, that mainly contribute to the development of vessel dysfunction in atherosclerosis.…”
Section: Discussionsupporting
confidence: 80%
“…However, surprisingly, we suggested in the current study that TAS administration for 2 h prior to TNF-α incubation dramatically prevented the HUVECs from TNF-α-triggered apoptosis by suppressing the overexpression of inflammatory factors, decreasing the viable apoptotic cell ratio, suppressing DNA fragmentation, and reducing caspase-3 activation. In addition, inflammatory cytokine-induced injury is a critical aetiology of TNF-α-induced endothelial damage [33]. Our results verified that TNF-α administration substantially increased the levels of inflammatory cytokines, such as interleukins, MCP-1, MMP-2, and MMP-9, that mainly contribute to the development of vessel dysfunction in atherosclerosis.…”
Section: Discussionsupporting
confidence: 80%
“…HO-1 is an important inducible antioxidant enzyme in vascular tissue. Although recent studies have demonstrated that Nrf2 has a role in protecting against hyperoxic damage [18] and in angiogenesis [19, 20] in human endothelial cells, the underlying molecular mechanism by which allicin induces Nrf2 activation has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, arthritis treatment is targeted at the inflammatory components, leading to the alleviation of pain and swelling [ 24 ]. Several studies have demonstrated the anti-inflammatory properties of KP, HE, and AM [ 15 , 18 , 27 ] and/or their ingredients liriodendrin [ 16 , 28 ], betulin [ 29 , 30 ], and formononetrin [ 31 , 32 ]. Therefore, KBH-JP-040 from HE, KP, and AM was used in experimental rat chondrocytes and rabbit OA models in an effort to reduce inflammation, protect cartilage damage, relieve pain and improve joint pathology.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth pointing out that the pharmacological functions of many compounds from KP, especially kalopanaxsaponin-A, have been shown to inhibit the overexpression of TNF-α and IL-1β and downregulation of COX-2 expression via modulating NF-κB/AP-1 [ 17 , 18 , 41 ]; and that HE treatment suppressed TNF-α-induced overexpression of MMP-9 and downregulated the nuclear translocation and transcriptional activation of NF-κB, followed by suppression of I-κB degradation [ 15 ]. Friedman [ 21 ] also reported that HE extracts reduce the expression of the matrix metalloproteinases MMP-2, MMP-9, COX-2, and 5-LOX in cells, which are all overexpressed in arthritic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation